EVALUASI EFEKTIVITAS UNIT PRODUKSI DALAM MEMPERSIAPKAN KOMPETENSI KERJA SISWA SMK - Sutopo, Adi (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2012)
Tujuan penelitian ini adalah mengetahui: 1) keefektifan kegiatan bel-ajar mengajar; 2) peningkatan kemampuan kompetensi kerja siswa; 3) pe-manfaatan faktor pendukung dan mengatasi faktor penghambat unit pro-duksi (UP), serta dampaknya bagi SMK. Model penelitian menggunakan CIPP-Logic dengan mixed method designs. Populasi penelitian adalah SMKN RSBI-SBI rumpun teknologi yang memiliki unit produksi. Penentuan sam-pel dengan purposive sampling yaitu: SMKN 2 Yogyakarta, SMKN 2 Depok Sleman, SMKN 2 Pengasih Kulon Progo dan SMKN 2 Wonosari Gunung Kidul. Pengumpulan data menggunakan kuesioner, wawancara, observasi dan dokumentasi. Analisis data meliputi analisis deskriptif, model Miles-Huberman dan logical framework analysis. Hasil penelitian adalah: 1) sebagian besar UP aktif, namun sumbangan sebagai sarana pembelajaran dan sum-ber pembiayaan operasional relatif kecil; 2) sebagian besar program UP mampu menyelaraskan program kurikulum, namun pemanfaatan sarpras dan SDM belum optimal; 3) peningkatan pengetahuan dan keterampilan siswa tercapai, namun jumlahnya terbatas; 4) keefektifan sebagai sarana pembelajaran tercapai, namun jumlah siswa dan guru yang terlibat relatif kecil; 5) kualitas konstruksi dan bahan tinggi serta harga jual standar, na-mun kualitas tampilan belum maksimal; 6) menambah kesejahteraan warga sekolah, dan pendapatan sekolah; dan 7) sebagian besar UP dipercaya ma-syarakat/industri.Kata kunci: unit produksi, kemampuan kompetensi kerja, sekolah menengah kejuruan______________________________________________________________AN EVALUATION OF THE EFFECTIVENESS OF PRODUCTION UNITS IN PREPARING STUDENTS' OCCUPATIONAL COMPETENCE ON VOCATIONAL HIGH SCHOOLSAbstractThis study aims to know: 1) the effectiveness teaching and learning; 2) the improvement of students' occupational competence, 3) the utilization of the facilitating factors and the hindering factors in the production units, and the impacts of the production units on VHSs. The research model used was the CIPP-Logic evaluation model with the mixed method designs. The research population comprised VHSs in the engineering cluster possessing production units in Yogyakarta Special Territory. The research sample was determined purposely, consisting of SMKN 2 Jetis Yogyakarta, SMKN 2 Depok Sleman, SMKN 2 Pengasih and SMKN 2 Wonosari. The quantitative and qualitative data were collected through questionnaires, in-depth inter-views, in-depth observations, and documents with reference. The data analysis employed a model by Miles-Huberman and logical frame-work analysis. The research findings are as follows. 1) Most of the production units are active, but their contributions as learning resources and as operational cost sources are relatively small. 2) Most of the production units are capable of adjusting the curricular programs to the production unit programs, but the utilization of the infrastructure facilities and human resources is not maximal. 3) improving students' knowledge and skills is reached but limited in number, 4) The effectiveness as learning resources for students is reached, but the students and teachers involved are limited in number. 5) The quality of construction and materials is high, the price is standard, but their performance is not maximum yet. 6) The production units can improve the welfare of school members and give the schools additional incomes. 7) Most of the production units are trusted bye indus-tries and society.Keywords: production units, occupational competence, vocational high schools